Effect of oil palm ash on the mechanical and thermal properties of unsaturated polyester composites - Sahari, Japar; Maleque, Md. Abdul (European Polymer Federation, 2016)
This research was carried out to evaluate the effect of oil palm ash (OPA) on the mechanical and thermal properties of biocomposites. Different compositions of OPA (i.e. 0, 10, 20 and 30 vol%) were introduced to unsaturated polyester (UPE) by using simple casting method with methyl ethyl ketone peroxide (MEKP) as a hardener. The specimens were prepared based on ASTM D5083 standards for tensile testing. From the results, it was found that the mechanical properties of UPE/OPA composites were improved in modulus with increasing the OPA content. The physical properties of UPE/OPA were also investigated where the density of biocomposites decrease with increasing OPA while the water absorption of UPE/OPA increase with increasing OPA. The thermal and morphological characterization of the UPE/OPA composites have been done using TGA, DSC and SEM.